Hyperlactatemia, Lactate Kinetics and Prediction of Citrate Accumulation in Critically Ill Patients Undergoing Continuous Renal Replacement Therapy With Regional Citrate Anticoagulation. Issue 9 (September 2017) - Khadzhynov, Dmytro; Dahlinger, Annette; Schelter, Christin; Peters, Harm; Kindgen-Milles, Detlef; Budde, Klemens; Lehner, Lukas Johannes; Halleck, Fabian; Staeck, Oliver; Slowinski, Torsten
Abstract : Objectives: Citrate accumulation is a major complication of regional citrate anticoagulation during continuous renal replacement therapy. We studied the prediction of citrate accumulation during continuous veno-venous hemodialysis with regional citrate anticoagulation by initial lactate concentrations and lactate kinetics. Design: A retrospective follow-up analysis from a cohort of critically ill patients. Setting: Mixed medical-surgical ICUs at a university hospital. Patients: All adult patients with acute kidney injury and treated with regional citrate anticoagulation-continuous veno-venous hemodialysis during a 3-year period ( n = 1, 070) were included in this retrospective study and screened for metabolic signs of citrate accumulation. Interventions: None. Measurements and Main Results: The frequency of citrate accumulation during the first 48 hours of therapy was 2.26%. In patients with initial normal lactate (< 2.2 mmol/L), elevated lactate (≥ 2.2 to < 4 mmol/L), or severe hyperlactatemia (≥ 4 mmol/L), the frequency of citrate accumulation was 0.77%, 2.70%, and 6.33%, respectively. Receiver operating characteristics-area under the curve of initial lactate concentration was 0.789 for the prediction of citrate accumulation. Optimal cutoff from receiver operating characteristics (2.39 mmol/L) showed strong negative prediction (99.28%), but weak positive prediction (5.21%). The slope intercept of lactate kinetics over 48 hours was positive and significantly higher in patients with citrate accumulation compared to those without (+0.2 vs –0.006 mmol/L/hr; p < 0.001). In patients with initial severe hyperlactatemia (≥ 4 mmol/L), the median calculated lactate clearance at 6, 12, and 18 hours was 24.0%, 48.1%, and 59.4% in the nonaccumulation group. These clearance rates were significantly higher at each time-point compared to patients with citrate accumulation (–9.8%, –20.5%, and 2.3%, respectively; p < 0.001 for each time-point). The highest receiver operating characteristics-area under the curve for citrate accumulation was observed for 12-hour values of lactate clearance (area under the curve = 0.839; 95% CI, 0.751–0.927) with an optimal cut-off value of 24.3%. Conclusions: Risk of citrate accumulation during regional citrate anticoagulation in a well-selected cohort of patients is low even in case of initial severe hyperlactatemia. Lactate kinetics rather than initially elevated lactate concentration should be considered in assessing the risk of citrate accumulation. Abstract : Supplemental Digital Content is available in the text.